Evaluación del posicionamiento de las Cooperativas de Ahorro y Crédito de la ciudad de Nueva Loja y su incidencia en el desarrollo local en el año 2014. - López Martínez, Cintia Daniela (2016)
This investigation research seeks to determine the impact of the Credit Unions (6 credit unions) on the life quality that is generated in the trade of Nueva Loja city. With this objective we part from the popular and solidarity economy history, organization, and regulation of the Ecuadorian financial current system. On the other hand, theories concerning to the management of economic resources are also reviewed. In the context of these and other limitations, the Credit Unions have become one of the fundamental axes of the country's economy by directing its efforts to the attention to small traders who every day strive for better life conditions. For this reason this research has as a main objective: to determine the importance of the Credit Union in the improving of the population welfare through debt financing. The first chapter is disclosed by the reference framework, the problem to be studied in the research, objectives, justification and importance of it. Second chapter consists of theoretical and conceptual framework that enabled to expand knowledge of the problem under study and influence of each one of the variables. Third Chapter: the methodological framework, type, research design, techniques and research tools, sample and data processing was determined. In the fourth chapter the conclusions and recommendations found in the research are developed. Finally in the fifth and final chapter discloses the literature that I used to support this research.